Saliva stress biomarkers in ERCP trainees before and after familiarisation with ERCP on a virtual simulator - Konstantinos Georgiou; Nikola Boyanov; Dimitrios Thanasas; Gabriel Sandblom; Gabriel Sandblom; Dimitrios Linardoutsos; Lars Enochsson; Lars Enochsson (Frontiers in Surgery, 2024)
BackgroundStress during the early ERCP learning curve may interfere with acquisition of skills during training. The purpose of this study was to compare stress biomarkers in the saliva of trainees before and after familiarisation with ERCP exercises on a virtual simulator.MethodsAltogether 26 endoscopists under training, 14 women and 12 men, completed the three phases of this study: Phase 1. Three different ERCP procedures were performed on the simulator. Saliva for α-amylase (sAA), Chromogranin A (sCgA), and Cortisol (sC) were collected before (baseline), halfway through the exercise (ex.), and 10 min after completion of the exercise (comp.); Phase 2. A three-week familiarisation period where at least 30 different cases were performed on the virtual ERCP simulator; and Phase 3. Identical to Phase 1 where saliva samples were once again collected at baseline, during, and after the exercise. Percentage differences in biomarker levels between baseline and exercise (Diffex) and between baseline and completion (Diffcomp) during Phase 1 and Phase 3 were calculated for each stress marker.ResultsMean % changes, Diffex and Diffcomp, were significantly positive (p < 0.05) for all markers in both Phase 1 and Phase 3. Diffex in Phase 1 was significantly greater than Diffex in Phase 3 (p < 0.05) for sAA and sCgA. Diffcomp for sAA in Phase 1 was significantly greater than Diffcomp in Phase 3 (p < 0.05). No significant differences were found in sC concentration between Phases 1 and 3.ConclusionThis study shows that familiarisation with the ERCP simulator greatly reduced stress as measured by the three saliva stress biomarkers used with sAA being the best. It also suggests that familiarisation with an ERCP simulator might reduce stress in the clinical setting.